2015
DOI: 10.1007/s00259-015-3260-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of EGFR and CD44v6 for prediction and response monitoring of HSP90 inhibition in an in vivo squamous cell carcinoma model

Abstract: PurposeHeat shock protein 90 (HSP90) is essential for the activation and stabilization of numerous oncogenic client proteins. AT13387 is a novel HSP90 inhibitor promoting degradation of oncogenic proteins upon binding, and may also act as a radiosensitizer. For optimal treatment there is, however, the need for identification of biomarkers for patient stratification and therapeutic response monitoring, and to find suitable targets for combination treatments. The aim of this study was to assess the response of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…The higher CD44v6-density on HCT116 cells was in line with results from LigandTracer analyses, where a clear signal was detected from HCT116 cells, whereas the signal from UM-SCC-74B cells was below the detection limit of the LigandTracer instrument. This supports previous studies assessing the CD44v6-antigen expression of these cell lines, verifying that CD44v6-antigen density on HCT116 and UM-SCC-74B cells can be considered moderate and low, respectively [27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…The higher CD44v6-density on HCT116 cells was in line with results from LigandTracer analyses, where a clear signal was detected from HCT116 cells, whereas the signal from UM-SCC-74B cells was below the detection limit of the LigandTracer instrument. This supports previous studies assessing the CD44v6-antigen expression of these cell lines, verifying that CD44v6-antigen density on HCT116 and UM-SCC-74B cells can be considered moderate and low, respectively [27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…The receptor expression was reduced by more than 50% in the named groups. The downregulation of HSP90 as well as its client proteins is a very attractive measure for treatment efficacy in vivo and expression levels of EGFR or HER2 among others have been assessed for treatment response monitoring with molecular imaging techniques like PET and SPECT cameras [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…As Onalespib can influence angiogenesis and the expression of numerous client proteins [32,33], the binding and spatial distribution of 177 Lu-DOTATATE after Onalespib treatment as well as expression of SSTR2 was investigated. Ex vivo autoradiography of BON tumor sections 48 h after the last treatment revealed that Onalespib treatment did not alter the uptake of 177 Lu-DOTATATE in the assessed sections (Fig.…”
Section: Lu-dotatate Selectivity and Distributionmentioning
confidence: 99%
“…EGFR and VEGFR are HSP90 client proteins and can be used to assess molecular responses after Onalespib therapy [15,30,33]. Here, the expression of EGFR and VEGFR was assessed in tumors with immunohistochemistry 48 h after the last treatment ( Fig.…”
Section: Molecular Response To Treatmentmentioning
confidence: 99%